Numerical Study on the Strongly Swirling Aerodynamic Field in an Isothermal Vortex Combustor - Smith Eiamsa-ard; Pongjet Promvonge (Agriculture and Natural Resources, 2006)
This research presented the application of a mathematical model for simulation of turbulent strongly swirling confined flow in an isothermal vortex combustor. Computations, based on a finite volume method, were carried out by utilizing the standard k-ε model and a simplified Algebraic Reynolds Stress Model (ASM) together with three discretization schemes, namely upwind, hybrid and QUICK. The work was performed in order to provide an understanding of physical behaviour of the swirling flow in a cold model vortex combustor. The ASM for steady compressible flows was used to predict the flow and was compared with the k-ε turbulence model. The calculated axial and tangential velocity profiles were compared with available measurement data. The mean flow patterns were shown in terms of contour plots. The prediction result showed that the ASM was better than standard k-ε model and the ASM together with QUICK results gave good agreement with the measurement data. Moreover, influences of the grid mesh distribution and the value of β were also studied.